IMPLEMENTASI PROJECT-BASED LEARNING DALAM PENGUATAN PEMAHAMAN LINGKUNGAN: STUDI PADA KEGIATAN PLP 1 DI SEKOLAH DASAR - Yulanti S. Mooduto; Rahmatia Syahrain (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammdiyah Gorontalo, 2025)
Environmental education at the elementary level plays a fundamental role in shaping students’ ecological awareness and responsible behavior. However, students’ conceptual understanding often remains limited when learning is dominated by conventional instruction. This study aims to describe the implementation of Project-Based Learning in strengthening students’ understanding of environmental concepts within the context of the School Field Introduction Program (PLP 1). This research employed a qualitative descriptive approach involving fourth- and fifth-grade students at SDN 17 Limboto. Data were collected through classroom observations, semi-structured interviews, and documentation during project-based environmental activities. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings show that Project-Based Learning enhances students’ engagement, contextual understanding, collaboration, and environmental awareness through authentic projects such as waste sorting, poster creation, and school cleanliness campaigns. The learning process helped students move from basic conceptual knowledge to reflective and applicative understanding. Therefore, Project-Based Learning can be considered an effective and contextually relevant strategy for strengthening environmental conceptual understanding in elementary education, particularly within experiential programs such as PLP 1.